Analysis of visual elements of leisure attractiveness of Slovenian landscapes - Cigale, Dejan (Geografski vestnik, 2021)
This paper discusses the attractiveness of the Slovenian landscape as a leisure space. It focuses in particular on relationship of attractiveness with landscape diversity and naturalness. As a starting point, thestudy of Perko et al. (2017) was used in which the authors identified the most and the least diverse Slovenian areas, i.e. landscape hotpots and coldspots. An online survey was conducted using photographs taken inselected hotspots and coldspots. Respondents were asked to rate the attractiveness of the landscapes shown in the photographs as destinations for a leisure trip. The attractiveness of the landscapes did not differ depending on whether they were in a hotspot or coldspot. On the other hand, the results clearly indicate the higher attractiveness of landscapes in which relatively natural landscape elements predominate.
Keywords: geografija; geography of tourism; landscape attractiveness; landscape diversity; landscape hotspots; naturalness; recreation; rekreacija; Slovenia; Slovenija; turistične destinacije; turizem